2006
DOI: 10.1139/x06-057
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effects of stand thinning on microclimates with semiparametric smoothing splines

Abstract: Monitoring the effects of stand thinning on microclimates is an integral part of any thinning experiment. It is through its modifications of microclimates that thinning alters important ecological processes. An efficient analysis of microclimate-monitoring data should address both the effects of thinning regimes on, and the temporal response trends of, microclimates. Probably because of the difficulties in modeling temporal trends parametrically, an examination of the existing literature on thinning showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Residuals diagnostics indicated that none of the residuals from the fitted models significantly violated the independence, equal variance, and normality assumptions. Details on using semiparametric smoothing splines to analyze four of the six microclimatic variables can be found in Guan et al (2006).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Residuals diagnostics indicated that none of the residuals from the fitted models significantly violated the independence, equal variance, and normality assumptions. Details on using semiparametric smoothing splines to analyze four of the six microclimatic variables can be found in Guan et al (2006).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Mixed-effects models and nonparametric modeling approaches can also be merged to produce semi-parametric and non-parametric mixed-effects models. Verbyla et al (1999) used smoothing splines to analyze longitudinal experiments, and Guan et al (2005) applied a semi-parametric mixed-effects model based on smoothing splines to analyze effects of thinning on microclimates. Such techniques have the potential to contribute significantly to the way in which sustainability data is analyzed in the future.…”
Section: Nonparametric Statistical Approachesmentioning
confidence: 99%
“…Sin embargo, la mayoría de trabajos evalúan el efecto de los tratamientos selvícolas mediante técnicas estadísticas que no tienen en cuenta la autocorrelación temporal. Este enfoque es incompleto ya que no se analiza el efecto de estos tratamientos sobre la dinámica de la variable (Guan et al, 2006). La escasez de estudios que evalúen cómo el manejo selvícola modifica la estructura temporal de estas variables ha sido explicada por la dificultad de modelar tendencias no lineales (Guan et al, 2006).…”
Section: Introductionunclassified
“…Este enfoque es incompleto ya que no se analiza el efecto de estos tratamientos sobre la dinámica de la variable (Guan et al, 2006). La escasez de estudios que evalúen cómo el manejo selvícola modifica la estructura temporal de estas variables ha sido explicada por la dificultad de modelar tendencias no lineales (Guan et al, 2006). Es posible que también haya influido, al menos parcialmente, la ausencia de series de datos continuas y largas.…”
Section: Introductionunclassified